Analisis Kualitas Produk dan Gaya Hidup dalam Membentuk Keputusan Pembelian Produk Sunscreen - Wijaya, Noval; Zahrah, Halimah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The skincare industry in Indonesia is experiencing rapid growth as public awareness of the importance of skin protection increases. Wardah, as a popular local brand, faces intense competition, making product quality and consumer lifestyle important factors influencing sunscreen purchasing decisions. This study aims to analyze the influence of product quality and lifestyle on Wardah sunscreen purchasing decisions. The research method used a quantitative approach through distributing questionnaires to Wardah sunscreen users. Data were analyzed using multiple linear regression to test the partial and simultaneous effects between variables. The results showed that product quality and lifestyle had a positive and significant effect, both partially and simultaneously, on Wardah sunscreen purchasing decisions. This finding underscores the importance of improving formulation quality and adapting marketing strategies to consumer lifestyles to increase purchasing interest. Practically, these findings can be used by companies to design product quality improvement strategies and marketing approaches that align with the lifestyles of young consumers, particularly college students.